Deteksi Bakteri Selulolitik pada Kotoran Luwak (Paradoxurus hermaphroditus) dari Kebun Binatang Bandung - Rikhsan Kurniatuhadi, Shinta Rahayu Rahmawati, (Jurnal Protobiont, 2018)
Cellulolytic bacteria were a group of bacteria involved in coffee fermentation in the digestive tract of civet (Paradoxurus hermaphroditus). The aim of this research was to detect the presence of cellulolytic bacteria isolated from civet feces. This research was conducted from December 2015 to February 2016. Samples of civet feces were collected from Bandung Zoo. Bacteria were isolated from civet feces and screened for cellulolytic activity in Carboxy Methyl Cellulose (CMC) media. Positive result for cellulose producing activity was indicated by the formation of clear zone around the colony. Characterization of the isolated bacteria was done based on macroscopic and microscopic observations followed by biochemical test. A total of 9 genera of cellulolytic bacteria were identified from the civet feces samples, such as Xylophilus (BSKL 1), Caryophanon (BSKL 2), Aeromicrobium (BSKL 3), Exiguobacterium (BSKL 4, BSKL 11), Brochotrix (BSKL 5), Alcaligenes (BSKL 6), Alteromonas (BSKL 7), Halomonas (BSKL 8), Chromobacterium (BSKL 9), Corynebacterium (BSKL 10, BSKL 13), Cellulomonas (BSKL 14) and BSKL isolates 12.